2014
DOI: 10.11648/j.ajhr.20140205.15
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinant Factors of Intestinal Parasites among School Children in Arba Minch Town, Southern Ethiopia

Abstract: Back ground: Intestinal parasitic infections are still quite common in developing countries including Ethiopia, particularly in children. They are mostly associated with unsafe and low quality of drinking water, poor personal and environmental sanitation. Thus, the objective of this study was to assess the prevalence and determinant factors of intestinal parasites among school children. Methods: A cross sectional study was conducted in March, 2014, among 498 students selected from three governmental elementary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
55
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(88 citation statements)
references
References 16 publications
25
55
8
Order By: Relevance
“…E. histolytica and G. lambila were the predominant protozoan parasites while Hookworm was the commonest helminth parasite. In other studies also E. histolytica and G. lambila were the commonly detected protozoan parasites [2,[10][11][12][13]. With regard to helminth parasites, in contrast to our study A. lumbricoides [9][10][11][12] was the commonest parasite in other studies.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…E. histolytica and G. lambila were the predominant protozoan parasites while Hookworm was the commonest helminth parasite. In other studies also E. histolytica and G. lambila were the commonly detected protozoan parasites [2,[10][11][12][13]. With regard to helminth parasites, in contrast to our study A. lumbricoides [9][10][11][12] was the commonest parasite in other studies.…”
Section: Discussioncontrasting
confidence: 93%
“…Studies from different part of Ethiopia [2,5,[9][10][11][12] and outside Ethiopia [4,7] reported a prevalence of 22.7-79.8%. There was higher prevalence in this study compared to studies conducted in India and Nepal [4,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in the line withSaka et al, (2014) (55) , andHaftu et al, (2014) (33) . On the other hand Al-Mohammed et al, (2010) (56) , and Sah et al, (2013) (57) found that hand washing after defecation was significantly associated with the prevalence of intestinal parasitic infection.…”
Section: Discussionsupporting
confidence: 92%
“…However, Tetteh (2012) (32) , who found that about (48.42%) of the studied students were males and about (51.58%) of them were females with the ages from 5-12 years. Also, another study done by Haftu et al, (2014) (33) , revealed that (48.8%) of the studied children were males and (51.2%) were females with a mean 10.72(+2.55) years. this difference in age may be due to change of age at starting of elementary education in different countries.Regarding history of parasitic infections, the present study revealed that less than two thirds of the studied students had previous personal history of parasitic infection (table 2).…”
Section: Discussionmentioning
confidence: 73%